The Impact of Organizational Culture on Knowledge Management Practices - Wanjala, Meredith (European Journal of Information and Knowledge Management, 2024)
Purpose: This study sought to examine the impact of organizational culture on knowledge management practices. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the impact of organizational culture on knowledge management practices. Preliminary empirical revealed that organizational culture significantly influenced knowledge management practices, with supportive cultures enhancing knowledge creation, sharing, and utilization, while rigid cultures hindered these processes. It found a symbiotic relationship where effective knowledge management reinforced a positive culture and vice versa. Leadership played a crucial role in fostering a knowledge-friendly culture, and strategic interventions were necessary to align cultural attributes with knowledge management goals. Practical implications included conducting cultural assessments and leveraging technology to facilitate communication and collaboration. Unique Contribution to Theory, Practice and Policy: The Theory of Organizational Culture by Edgar Schein, SECI Model (Socialization, Externalization, Combination, Internalization) by Nonaka and Takeuchi and the Knowledge-Based View (KBV) of the Firm by Grant may be used to anchor future studies on the impact of organizational culture on knowledge management practices. The study highlighted the importance of integrating cultural dimensions into existing KM theories, emphasizing the need for a supportive culture that promotes open communication and collaboration. It recommended practical steps such as team-building activities, cross-functional teams, and the adoption of technology aligned with cultural initiatives. The study also underscored the need for policies that recognize and reward knowledge-sharing behaviors, reduce hierarchical barriers, and promote inclusiveness. These recommendations aimed to enhance KM practices by embedding them into organizational culture, thereby improving efficiency, innovation, and sustained competitive advantage.